159: ASSESSMENT OF THE QUALITY OF REPORTING ON RANDOMIZED CONTROLLED TRIALS IN DIABETES BETWEEN HIGH AND LOW IMPACT FACTOR AND SJR JOURNALS. (8th February 2017) - Aletaha, Azadeh; Soltani, Akbar; Baradaran, Hamid Reza
Abstract : Background and aims: The primary objective of this study was to evaluate the quality of randomized controlled clinical trial reports in diabetes research in Iran and the secondary objective included identifying any associations between CONSORT quality and surrogate markers of article quality, including high and low impact factor and SJR journals. Methods: 184 RCTs studies conducted on Diabetes mellitus in Iran. ANOVA and Pearson correlation was used to analyze the relationship among group with each article for reports of (RCTs) conducted on Diabetes mellitus that were index in ISI, Scopus, PubMed or other international journals index based an impact factor and SJR index. For the purposes of this study, we selected all articles published in English and indexed in PubMed, ISI, Scopus and other international journals between 2004 to 2014. Results: In all, 269 articles were retrieved from the search of the ten databases. Of these, 184 articles were selected. The mean CONSORT score of the 184 RCTs was 8.11 out of 17 (31.7%, range 6–12, SD 1.38). The poorest-reported items were all item. No paper adequately reported all items in the CONSORT checklist. There was no correlation between the quality of CONSORT score and the IF and SJR Journals (Pearson:-0.065, P: 3.84.29). In addition, there was no statistical difference in CONSORT score between group and within group IF or SJR journal designs (ANOVA: P value: 0.7, the mean CONSORT score of the 184 RCTs was 8.63 from 17 scores). Conclusion: In conclusion, our findings suggest that the that the authors, funding agencies, peer reviewers, and journal-editors in RCTs in diabetes has an important role to enhance the quality of RCTs and collaborate to enhance the integration of CONSORT into the RCT publication process Evolution and further extension of CONSORT will hopefully help to incorporate studies with alternative methodologies.